A commentary on "the role of services in the future". Issue 1 (2nd January 2021) - Cronin Jr, J. Joseph
ABSTRACT: The goal of this commentary is to promote the critical thinking and research needed to better understand the challenges that face scholars and practitioners relative to the role of services in the future. Factors creating the need for a reevaluation of existing service options are identified. Suggestions for research related to the role of services in the future are also presented. In addition, opportunities for such research are offered as research directives.